ANALISIS KELAYAKAN FINANSIAL DAN SENSISTIVITAS USAHA TAMBAK UDANG VANAME DI KECAMATAN KETAPANG KABUPATEN LAMPUNG SELATAN - Pingky Dwi Septiana; Muhammad Irfan Affandi; Serly Silvianti (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
The purpose of this study was to determine the feasibility of vaname shrimp farming. This research was conducted in Ketapang District, South Lampung Regency in January, 2018. The samples were 35 shrimp farmers chosen usinga cluster propotionalsimple random sampling method based on their cultivation technology, i.e.traditional, semi-intensive and intensive. The research data were analyzed using the method of financial feasibility analysis and sensitivity analysis. The results showed that the vaname pondshrimp business in a traditional, semi-intensive and intensive manner was feasible to be cultivated and developed based on the criteria of NPV, IRR, Gross B/C, Net B/C, and PP. However, the results of calculations show that the business ofintensive vaname shrimp business is more feasible and profitable than semi-intensive and traditional vaname shrimp businesses. Based on the results of the sensitivity analysis, after an increase in production costs, and a decrease in the production and price of vaname shrimp, the business is still worth cultivated and developed. The sensitivity rate shows that most investment criteria are sensitive to change. Some investment criteria that are not sensitive to changes are PP, Gross B/C, and Net B/C.Key words: farm, feasibility, finance, sensitivity, vaname